Retinal blood vessel diameters in children and adults exposed to a simulated altitude of 3,000 m - Mlinar, Tinkara; Debevec, Tadej; Kapus, Jernej; Najdenov, Peter; McDonnell, Adam C.; Ušaj, Anton; Mekjavic, Igor B.; Jaki Mekjavic, Polona (Frontiers in Physiology, 2023)
Introduction: Technological advances have made high-altitude ski slopes easily accessible to skiers of all ages. However, research on the effects of hypoxia experienced during excursions to such altitudes on physiological systems, including the ocular system, in children is scarce. Retinal vessels are embryologically of the same origin as vessels in the brain, and have similar anatomical and physiological characteristics. Thus, any hypoxia-related changes in the morphology of the former may reflect the status of the latter. Objective: To compare the effect of one-day hypoxic exposure, equivalent to the elevation of high-altitude ski resorts in North America and Europe ( 3000 m), on retinal vessel diameter between adults and children. Methods: 11 adults (age: 40.1 ± 4.1 yrs) and 8 children (age: 9.3 ± 1.3 yrs) took part in the study. They spent three days at the Olympic Sports Centre Planica (Slovenia; altitude: 940 m). During days 1 and 2 they were exposed to normoxia (FiO2 = 0.209), and day 3 to normobaric hypoxia (FiO2 = 0.162 ± 0.03). Digital high-resolution retinal fundus photographs were obtained in normoxia (Day 2) and hypoxia (Day 3). Central retinal arteriolar (CRAE) and venular equivalents (CRVE) were determined using an Automated Retinal Image Analyser. Results: CRAE and CRVE increased with hypoxia in children (CRAE: normoxia: 105.32 ± 7.72 µm, hypoxia: 110.13 ± 7.16 µm, CRVE: normoxia: 123.39 ± 8.34 µm, hypoxia: 130.11 ± 8.54 µm) and adults (CRAE: normoxia: 105.35 ± 10.67 µm, hypoxia: 110.77 ± 8.36 µm; CRVE: normoxia: 126.89 ± 7.24 µm, hypoxia: 132.03 ± 9.72 µm), with no main effect of group or group*condition interaction. A main effect of condition on CRAE and CRVE was observed (CRAE: normoxia: 105.34 ± 9.30 µm, hypoxia: 110.50 ± 7.67 µm, p < 0.001; CRVE: normoxia: 125.41 ± 7.70 µm, hypoxia: 131.22 ± 9.05 µm, p < 0.001). Conclusion: A 20-hour hypoxic exposure significantly increased CRAE and CRVE in adults and children. These hypoxia-induced increases were not significantly different between the age groups, confirming that vasomotor sensitivity of the retinal vessels to acute hypoxia is comparable between adults and prepubertal children.